E-Government in Malaysia : a study on user adoption of e-Services / Noor Dalila Noor Rashid - Noor Rashid, Noor Dalila (Faculty of Computer and Mathematical Sciences, 2007)
This research studied the E-Govemance, E-Govemment and E-Services in Malaysia with emphasis given on E-Services adoption. What makes people adopt and use the E-Services has not been researched deeply. This study aims to fill this gap. The objectives of this research are to determine the drivers and inhibitors of E-Services adoption, to determine the adoption level of E-Services, and to develop an E-Services adoption model. Based on extensive literature review, eight factors that drives and inhibit adoption had been identified and E-Services adoption model was developed. The model was tested using a survey of 171 users of E-Services in Malaysia. The survey was carried out using convenience sampling method and through e-mails. Model developed was used to determine the relationship between factors such as Relative Advantage, Compatibility, Tnalability, Observability, Complexity, Security Concern, Privacy Concern, and IT Illiteracy with adoption. A Pearson's Correlation Coeffiecient analysis showed that all the eight factors have influence in E-Services adoption with four factors which are Relative Advantage, Compatibility, Trialability, and Observability positively related to adoption whilst another four negatively related to adoption. The factors that negatively associated with adoption are Complexity, Security Concern, Privacy Concem,and IT Illiteracy. Supported by the analysis result, an E-Services adoption model was proposed. This research concludes with discussion of these results, study limitations, and recommendations for future research directions.